Experimental Study on Fabrication of Environment-Friendly Concrete by Solidifying Aeolian Sand and Natural Gravel with Fly Ash-Based Geopolymer - Shi-Yu Guan; Bin-Peng Tang; Xie-Dong Zhang; Ying-Qi Liu; Zheng-Xun Yang (Buildings)
To tackle the shortage of river sand resources and excessive carbon emissions in building materials, environment-friendly concrete can be fabricated by solidifying aeolian sand and natural gravel with a fly ash-based geopolymer. Aeolian sand and natural gravel are accessible building materials, but their engineering applications are largely limited by their poor properties such as high mud content, large specific surface area, and discontinuous particle size distribution. To enhance the application of this environment-friendly concrete, in this paper, 48 sets of specimens with different geopolymer dosages, curing temperatures, and curing times are studied experimentally, and quite well-strengthened geopolymer aeolian sand mortar (GAM), geopolymer aeolian sand concrete (GAC), and an appropriate dosage of the geopolymer are finally obtained. The experimental results and the failure section of the mortar specimen indicate that the fly ash geopolymer can solidify the aeolian sand and ensure the integrity and compactness of the specimen. The 28-day compressive and flexural strength of the geopolymer standard sand mortar (GSM) reached 40.5 MPa and 4.3 MPa, respectively, at a curing temperature of 60 °C when the amount of alkali activator was improved to 100%, and the 28-day compressive and flexural strength of GAM reached 33.7 MPa and 4.2 MPa, respectively, when the amount of geopolymer material was 0.75 times that of aeolian sand. A lower compressive strength of GAC was obtained following the addition of aeolian sand. The experiment results can provide a reference for aeolian sand usage and have a certain social value in environmental protection.